Operando experimental evidence on the central role of oxygen vacancies during methane combustion - Farahani, Majid D.; Wolf, Moritz; P.O. Mkhwanazi, Thabiso; Claeys, Michael; Friedrich, Holger B. (Journal of Catalysis, 2020)
Catalytic methane combustion is an important reaction for many industries active in energy domains, since methane is a greenhouse gas and has a high H/C ratio, which makes it a suitable replacement for oil and coal. Here, operando magnetometry, unsteady state propane dehydrogenation, XPS analysis and temperature programmed desorption of oxygen species are applied to investigate the parameters affecting methane combustion in situ using inexpensive bimetallic ferrite spinels as catalysts. Also, fresh, post catalytic and operando characterizations of the catalysts showed that oxygen vacancies are a key factor for the generation of activated interfacial oxygen species, which facilitates the dehydrogenation mechanism. Here, nickel ferrite outperformed cobalt, copper, and zinc ferrite, in methane combustion, as it displays superior thermal stability and benefits from a synergy between different active sites. NiFe2O4 provides oxygen vacancies and partially reduced metal sites with dehydrogenation ability that participate in H abstraction from methane (rate determining step).
Created from Fastlane, Scopus look-up
Keywords: Dehydrogenation; Ferrite spinels; Operando methane combustion; Oxygen vacancy; Sintering mechanism; Solution combustion synthesis